Predator prize - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Dr Hans Herren, Director of the International Centre for Insect Physiology and Ecology (ICIPE), has won the 1995 World Food Prize in recognition for his work in the field of biological control, in particular for his work on the control of a major...